Graphene-passivated nickel as an efficient hole-injecting electrode for large area organic semiconductor devices - Di Nuzzo, Daniele; Mizuta, Ryo; Nakanishi, Kenichi; Martin, Marie-Blandine; Aria, Adrianus Indrat; Weatherup, Robert; Friend, Richard H.; Hofmann, Stephan; Alexander-Webber, Jack (American Institute of Physics (AIP), 2020)
Efficient injection of charge from metal electrodes into semiconductors is of paramount importance to obtain high performance optoelectronic devices. The quality of the interface between the electrode and the semiconductor must, therefore, be carefully controlled. The case of organic semiconductors presents specific problems: ambient deposition techniques, such as solution processing, restrict the choice of electrodes to those not prone to oxidation, limiting potential applications. Additionally, damage to the semiconductor in sputter coating or high temperature thermal evaporation poses an obstacle to the use of many device-relevant metals as top electrodes in vertical metal–semiconductor–metal structures, making it preferable to use them as bottom electrodes. Here, we propose a possible solution to these problems by implementing graphene-passivated nickel as an air stable bottom electrode in vertical devices comprising organic semiconductors. We use these passivated layers as hole-injecting bottom electrodes, and we show that efficient charge injection can be achieved into standard organic semiconducting polymers, owing to an oxide free nickel/graphene/polymer interface. Crucially, we fabricate our electrodes with low roughness, which, in turn, allows us to produce large area devices (of the order of millimeter squares) without electrical shorts occurring. Our results make these graphene-passivated ferromagnetic electrodes a promising approach for large area organic optoelectronic and spintronic devices.